(untitled) (Plant Tissue Culture and Biotechnology, 2010)
A histological study of the indirect organogenesis from internodal cultures of Gloriosa superba L. showed that the callus initiated from the subepidermal cells. The organogenic and non organogenic callii are the result of hormonal variation in the medium. In non organogenic callus cells redifferentiated into xylem elements forming clusters of nest like structures. In organogenic callus, cells redifferen-tiated into nodules of meristemoids which further differentiated into shoot apical meristem. Keywords: Histological marker, Gloriosa superba, Organogenic calli D.O.I. 10.3329/ptcb.v20i1.5957 Plant Tissue Cult. & Biotech. 20(1): 1-5, 2010 (June)